Image: the power of deterrence and coercion - Brandão, Jack (Revista Digital do LAV, 2025)
This article underscores the crucial needto comprehend the etymological issue of the term image,particularly incomparison with the Greek terms eikón,eídolon,andLatin imago.It also delves into the image’s intimidating and coercive power,which has been harnessed for centuries.With this understanding, we aimto shed light onhow these terms were employed by Homer and Virgil, capturing their unique characteristics to unravelnot justthe concept itselfbut also its linguistic implications. This will enable us to viewthe image notmerelyas a deliberate copy of the external worldbut as a purposeful display ofstrength and power that has been utilized since Antiquity by numerous culturesand continues tobe effective today, as we will demonstrate.